Vericiguat: A New Hope for Heart Failure Patients - Raquel Chiles; Rami A. Al-Horani (Cardiovascular Therapeutics)
Heart failure with reduced ejection fraction (HFrEF) is the inability of the heart to adequately contract or eject blood. This heart is unable to produce adequate cardiac output to perfuse vital tissues. At a fundamental level, it is known that the cardioprotective pathway of nitric oxide-soluble guanylate cyclase-cyclic guanosine monophosphate is impaired in heart failure patients. Vericiguat is a novel, orally used, small molecule, and direct stimulator of the soluble guanylate cyclase, and thus, it enhances the production of cyclic guanosine monophosphate. Vericiguat was approved by the FDA in January of 2021 to reduce the risk of cardiovascular death and heart failure hospitalization following a hospitalization for heart failure or need for outpatient IV diuretics, in adults with symptomatic chronic heart failure and ejection fraction less than 45%. In this review, we describe the chemical and mechanistic aspects, pharmacokinetics, adverse effects, and contraindications of vericiguat so as to facilitate its optimal therapeutic use.